2013
DOI: 10.1128/iai.01035-12
|View full text |Cite
|
Sign up to set email alerts
|

Tetratricopeptide Repeat Motifs in the World of Bacterial Pathogens: Role in Virulence Mechanisms

Abstract: eThe tetratricopeptide repeat (TPR) structural motif is known to occur in a wide variety of proteins present in prokaryotic and eukaryotic organisms. The TPR motif represents an elegant module for the assembly of various multiprotein complexes, and thus, TPR-containing proteins often play roles in vital cell processes. As the TPR profile is well defined, the complete TPR protein repertoire of a bacterium with a known genomic sequence can be predicted. This provides a tremendous opportunity for investigators to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
151
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(161 citation statements)
references
References 76 publications
1
151
0
3
Order By: Relevance
“…Indeed, the occurrence of TPR in the FCBPs, but not in the CFBPs, parallels the greater prevalence of the TPR domains in eukaryotes over prokaryotes (Cerveny et al 2013).…”
Section: Modular and Unique Domain Arrangements Of The Dfismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the occurrence of TPR in the FCBPs, but not in the CFBPs, parallels the greater prevalence of the TPR domains in eukaryotes over prokaryotes (Cerveny et al 2013).…”
Section: Modular and Unique Domain Arrangements Of The Dfismentioning
confidence: 99%
“…Unique TPR signature of the FCBP family and its phylogenetic subsets TPR sequences are roughly 34 amino acid-long, degenerate repeats, in which the properties of key amino acids in specific positions, rather than the exact residues, are conserved (Cerveny et al 2013;D'Andrea and Regan 2003). Although TPRs occur in various number of repeats, a recent large-scale survey of all TPR-containing proteins in living organisms revealed that three-TPR (3TPR) is the most common, comprising~40% of all TPRs (Sawyer et al 2013).…”
Section: Gammaproteobacteriamentioning
confidence: 99%
“…Both ANKs and TPRs mediate protein-protein interactions and are known as eukaryote-like proteins (ELPs), in reference to their identification first in eukaryote genomes, but more recently also in many prokaryote genomes. TPRcontaining proteins are known to play critical roles as bacterial virulence factors (Cerveny et al, 2013), and their presence in the genome of a sponge Pseudovibrio sp. symbiont has been postulated to aid in attachment to the eukaryotic host and in avoidance of the host's immune response (Alex and Antunes, 2015).…”
Section: Differential Expression Analysis Of Sponge Genes Indicates Smentioning
confidence: 99%
“…TPR protein sequences are highly variable, although a core consensus sequence, W 4 -L 7 -G 8 -Y 11 -A 20 -F 24 -A 27 -P 32 , was identified two decades ago (24). None of the positions of the consensus are invariable, although hydrophobic residues are commonly observed at those positions (24)(25)(26). Of the three predicted TPR motifs in P. aeruginosa FimV, two are organized in tandem, proximal to the inner membrane (TPR1 and TPR2, residues 544 to 611), while the third (TPR3, residues 873 to 906) is at the C terminus, separated from TPR1 and TPR2 by a long, highly acidic region predicted to lack a regular secondary structure (17).…”
mentioning
confidence: 99%